2017
DOI: 10.18632/oncotarget.22569
|View full text |Cite
|
Sign up to set email alerts
|

SREBP-2-driven transcriptional activation of human SND1 oncogene

Abstract: Upregulation of Staphylococcal nuclease and tudor domain containing 1 (SND1) is linked to cancer progression and metastatic spread. Increasing evidence indicates that SND1 plays a role in lipid homeostasis. Recently, it has been shown that SND1-overexpressing hepatocellular carcinoma cells present an increased de novo cholesterol synthesis and cholesteryl ester accumulation. Here we reveal that SND1 oncogene is a novel target for SREBPs. Exposure of HepG2 cells to the cholesterol-lowering drug simvastatin or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…In this regard, our own work revealed that SND1 is a target gene for SREBPs. The activation of SREBP-2 in HepG2 cells cultured in the presence of the cholesterol synthesis inhibitor simvastatin or in a lipoprotein-deficient medium resulted in an increment of SND1 promoter activity and transcript levels (79). ChIP and mutational assays confirmed the functional binding of SREBP-2 to two sites in the proximal promoter sequence containing the SRE −60 and E-box −230 motifs while SREBP-1 binding is restricted to the region with the regulatory element SRE −60 (Figure 3B).…”
Section: The Snd1 Promotermentioning
confidence: 99%
“…In this regard, our own work revealed that SND1 is a target gene for SREBPs. The activation of SREBP-2 in HepG2 cells cultured in the presence of the cholesterol synthesis inhibitor simvastatin or in a lipoprotein-deficient medium resulted in an increment of SND1 promoter activity and transcript levels (79). ChIP and mutational assays confirmed the functional binding of SREBP-2 to two sites in the proximal promoter sequence containing the SRE −60 and E-box −230 motifs while SREBP-1 binding is restricted to the region with the regulatory element SRE −60 (Figure 3B).…”
Section: The Snd1 Promotermentioning
confidence: 99%
“…NF-κB binding site is located within the proximal 300 bp segment of SND1 promoter and confers TNFα-mediated induction of SND1 [13] [ Figure 1B]. SREBP-2 binds to a proximal promoter region containing a serum response element and an enhancer box motif and induces SND1 expression upon cholesterol depletion [16] . Activated Smad2 and Smad3 bind to SND1 promoter and confer TGFβ-medicated induction of SND1 expression [17] [ Figure 1B].…”
Section: Structure and Activationmentioning
confidence: 99%
“…Cholesterol is another component of the lipid core in both LDs and lipoproteins, the synthesis of which is regulated by SND1. Under conditions of cholesterol depletion, SREBP2, a regulator of cholesterol uptake and synthesis activates SND1 [16] . Overexpression of SND1 results in increased cholesterogenesis, metabolically coupled to cholesterol esterification, causing an increase in cholesteryl ester levels [57] .…”
Section: Role Of Snd1 In Lipid Metabolismmentioning
confidence: 99%
“…SREBP-2 and HMGCR were overexpressed in cisplatin-resistant A2780 epithelial ovarian cancer cells (Zheng et al, 2018). SREBP-2 promotes the expression of Staphylococcal nuclease and tudor domain containing 1 gene that is associated with the progression and malignancy of colon, breast, prostate, lung, glioma, skin, and liver cancers (Armengol et al, 2017), providing potential new applications for tocotrienols in cisplatin-resistant cancers. Mevalonate rescues the effect of statin, but not that of tocotrienol, on prostate cancer cell viability, consistent with tocotrienol-mediated increase in the degradation of nuclear, mature SREBP-2, which maintains cholesterol homeostasis through transcriptional regulation of enzymes in cholesterol biosynthesis and uptake beyond HMGCR (Krycer et al, 2012).…”
Section: Synergistic Effect Of Statins and Isoprenoids On Tumor Growtmentioning
confidence: 99%